Retrospective study of efficacy and adverse events of immune checkpoint inhibitors in 22 xeroderma pigmentosum patients with metastatic or unresectable cancers - Fernandez, Elvelyn R.; Tamura, Deborah; Khan, Sikandar G.; Momen, Sophie; Fassihi, Hiva; Sarkany, Robert; DiGiovanna, John J.; Kraemer, Kenneth H. (Frontiers in Oncology, 2023)
Background Xeroderma pigmentosum (XP), a rare disease with defects in DNA repair genes, has >1,000-fold increased risk of ultraviolet-induced skin cancers. Immune checkpoint inhibitors (ICIs) are used for treating cancers with large numbers of mutations but may also promote adverse events (AEs). Deficient DNA repair in XP patients may lead to increased numbers of mutations, leading to enhanced efficacy of cancer response or, alternatively, to increased AE in response to ICI. We sought to compare the efficacy and AE of ICI in XP patients with metastatic or unresectable cancers to that of ICI-treated patients in the general population. Methods In this retrospective study, we reviewed medical records of XP patients treated in the United States and in London (UK). We also reviewed published reports of ICI-treated XP patients and patients in the general population. Results Metastatic or unresectable cancers in all 22 (100%) XP patients showed regression or remission in response to ICI. The types and frequencies of AE in XP patients were similar to those reported among ICI-treated patients in the general population. However, two XP patients had concurrent additional cancers that did not respond to ICI, two XP patients had cancer recurrence or progression after initial response, and eight XP patients developed new skin cancers during or after ICI treatment. Conclusion In this retrospective study with small sample size, XP patients demonstrated positive responses to ICI and the treatment was well tolerated but some patients developed new skin cancers while being treated. ICIs can be considered in treating metastatic or unresectable cancers in XP patients.